Nutrition management of critically ill adult patients requiring non-invasive ventilation: a scoping review protocol. Issue 7 (20th July 2022) - Viner Smith, Elizabeth; Ridley, Emma J.; Rayner, Christopher K.; Chapple, Lee-anne S.
ABSTRACT: Objective: This scoping review will identify the current available literature and key concepts in the nutrition management of critically ill adult patients requiring non-invasive ventilation. Introduction: Current international nutrition guidelines include recommendations for the nutrition management of critically ill patients who are receiving invasive mechanical ventilation; however, these guidelines do not address nutrition management of patients receiving non-invasive ventilation. This scoping review aims to explore and describe the existing available literature on the nutrition management of critically ill adults requiring non-invasive ventilation. Inclusion criteria: This review will consider original research (qualitative, quantitative, or mixed methods studies) reporting on any nutrition parameter for critically ill adult patients (≥16 years) requiring non-invasive ventilation in the intensive care unit. Concepts of interest based on the general intensive care nutrition literature include route of nutrition, recommendations related to macro- or micro-nutrients, nutrition provision, barriers to nutrition provision, and strategies for nutrition management. Methods: This review will be conducted in accordance with JBI methodology for scoping reviews using a three-step search strategy. MEDLINE, Embase, Scopus, and Web of Science will be searched to obtain original research available in English and published after 1990. Google Scholar will be searched for gray literature. Duplicates will be removed and studies will be selected by two independent reviewers based on the inclusion criteria. The same two reviewers will extract data in duplicate using a data extraction tool. Any disagreements will be resolved via consensus with a third reviewer. Data extraction will be synthesized in tabular and diagrammatic format.